2010
DOI: 10.1002/jqs.1370
|View full text |Cite
|
Sign up to set email alerts
|

Annually resolved events of Younger Dryas glaciation in Lochaber (Glen Roy and Glen Spean), western Scottish Highlands

Abstract: This paper presents the results of micromorphological analysis of laminated sediments that accumulated in ice-dammed lakes in Lochaber (Glen Roy and vicinity) during the Younger Dryas (Loch Lomond) Stadial. These lakes were responsible for the formation of the famous 'Parallel Roads of Glen Roy' (Agassiz, 1840), prominent shorelines cut into the valley sides of Glen Roy and adjacent valleys. Annually deposited (varved) layers, which can be distinguished from other rhythmites by micromorphological examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 55 publications
3
62
0
Order By: Relevance
“…Here we report new evidence that provides more precise chronological constraints for growth of YD ice in the Loch Lomond Global and Planetary Change 79 (2011) (Palmer et al, 2010) and with some evidence for growth of the Main Inland Ice Sheet in Norway during the YD (Mangerud et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…Here we report new evidence that provides more precise chronological constraints for growth of YD ice in the Loch Lomond Global and Planetary Change 79 (2011) (Palmer et al, 2010) and with some evidence for growth of the Main Inland Ice Sheet in Norway during the YD (Mangerud et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…The only extensive body of research is found in the southwest corner of the region in the area around Glen Roy (e.g. Fabel, Small, Miguens-Rodriguez, & Freeman, 2010;Lowe & Cairns, 1991;Palmer, Rose, Lowe, & MacLeod, 2010, Palmer, Rose, & Rasmussen 2012Peacock, 1986;Sissons, 1978Sissons, , 1979Sissons & Cornish, 1983). As a result, the lack of systematic glacial geomorphological mapping across the Monadhliath Mountains as a whole has led to a restricted and inconsistent understanding of ice mass fluctuations and dynamics, with the majority of current knowledge constrained to the major valley systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several landslides in Glen Roy and Glen Gloy have also been linked to slope instability associated with the sudden draining of the lakes and the rapid unloading of the ground, while detailed levelling of the shorelines has demonstrated differential glacio-isostatic uplift and dislocation of crustal blocks Cornish, 1982a, 1982b). More recent studies have added to the scientific understanding and value of the area (Fabel et al, 2010;Macleod et al, 2011;Palmer et al, 2010Palmer et al, , 2012Ballantyne, 2012;Bendle et al, 2015;Boston and Lukas, 2016;Devine and Palmer, 2016;Sissons, 2016aSissons, , 2016b, with key issues also discussed during and following Quaternary Research Association (QRA) Field Meetings in 1989 and 2008 (Peacock and Cornish, 1989;Palmer et al, 2008;Peacock, 2009 …”
Section: Scientific Discovery Debate and Current Valuementioning
confidence: 99%